The Coping with Cyberbullying Questionnaire: development of a new measure - Mc Guckin, Conor (MDPI AG, 2016)
Victims of cyberbullying report a number of undesirable outcomes regarding their well-being, especially those who are not able to successfully cope with cybervictimization. Research on coping with cyberbullying has identified a number of different coping strategies that seem to be differentially adaptive in cases of cybervictimization. However, knowledge regarding the effectiveness of these strategies is scarce. This scarcity is partially due to the lack of valid and reliable instruments for the assessment of coping strategies in the context of cybervictimization. The present study outlines the development of the Coping With Cyberbullying Questionnaire and tests of its reliability and construct validity over a total of five questionnaire development stages. The CWCBQ was developed in the context of a longitudinal study carried out in Switzerland and was also used with Italian and Irish samples of adolescents. The results of these different studies and stages resulted in a questionnaire that is composed of seven subscales (i.e., distal advice, assertiveness, helplessness/self-blame, active ignoring, retaliation, close support, and technical coping) with a total of 36 items. The CWCBQ is still being developed, but results obtained so far suggested that the questionnaire was reliable and valid among the countries where it was used at different stages of its development. The CWCBQ is a promising tool for the understanding of potential coping with experiences of cybervictimization and for the development of prevention and intervention programs.
Cyberbullying: where are we now?: a cross-national understanding
Keywords: Cyberbullying; Cybervictimization; Bullying; EDUCATION; Communication; Education; Youth